1988
DOI: 10.1021/ed065p1029
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry in the comics: Part 1. A survey of the comic book literature.

Abstract: Collecting comic books is the fourth most common collection hobby. This article takes readers through the appearances of chemistry topics in comic books.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
1
9
0
2
Order By: Relevance
“…6 The subject "chemistry in the comics" was used to initiate discussion of various aspect of chemistry. 7 Two reviews of chemical cartoons for instructional purposes have appeared, one of which focused on pre-existing cartoons, 8 while the other discussed the use of both these and ones that students create. 9 In the latter review, it was concluded that cartoons are able to increase understanding, attention, motivation to learn, good attitudes, productivity, creativity, divergent thinking, and active participation learning while also reducing stress and boredom.…”
Section: ■ Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…6 The subject "chemistry in the comics" was used to initiate discussion of various aspect of chemistry. 7 Two reviews of chemical cartoons for instructional purposes have appeared, one of which focused on pre-existing cartoons, 8 while the other discussed the use of both these and ones that students create. 9 In the latter review, it was concluded that cartoons are able to increase understanding, attention, motivation to learn, good attitudes, productivity, creativity, divergent thinking, and active participation learning while also reducing stress and boredom.…”
Section: ■ Introductionsupporting
confidence: 69%
“…In the chemistry setting, it seems that relatively more attention has been given to existing cartoons for instructional purposes: for example, to present safety topics and to learn the difference between a strong and weak acid . The subject “chemistry in the comics” was used to initiate discussion of various aspect of chemistry . Two reviews of chemical cartoons for instructional purposes have appeared, one of which focused on pre-existing cartoons, while the other discussed the use of both these and ones that students create .…”
Section: Introductionmentioning
confidence: 99%
“…No universo da Química, as HQs tiveram seus primórdios com histórias de ficção científica com o uso de substâncias química imaginárias, como por exemplo, a contaminação por elemento radioativo do "Hulk" ou pelo poder de destruição da "criptonita" do "Superman" (AQUINO et al, 2015). Na década de 80 e 90 ocorreram publicações de quatro artigos intitulados: "Chemistry in the Comics" no Journal of Chemical Education (CARTER, 1988(CARTER, , 1989a(CARTER, , 1989b(CARTER, , 1990. Essas publicações destacaram os fatos históricos e anedotas interessantes sobre as HQs e o EQ.…”
Section: Ensino De Química E Histórias Em Quadrinhos: a Importância Desse Gênero No Ambiente Escolar E Acadêmicounclassified
“…O uso de histórias em quadrinhos em revistas estadunidenses envolvendo conteúdos químicos é debatido em quatro artigos intitulados "Chemistry in the Comics" no Journal of Chemical Education (CARTER, 1988(CARTER, , 1989a(CARTER, , 1989b(CARTER, , 1990. Neles observamos uma série de fatos históricos e anedotas interessantes sobre a química, o uso de conceitos e nomenclaturas da química por diversos personagens.…”
Section: História Em Quadrinhos No Ensino De Químicaunclassified